2020
DOI: 10.1101/2020.09.22.20199489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol transmission of COVID-19 and infection risk in indoor environments

Abstract: The role of aerosolized SARS-CoV-2 viruses in airborne transmission of COVID-19 is debated. The transmitting aerosol particles are generated through the breathing and vocalization by infectious subjects. Some authors state that this represents the dominant route of spreading, while others dismiss the option. Public health organizations generally categorize it as a secondary transmission pathway. Here we present a simple, easy-to-use spreadsheet algorithm to estimate the infection risk for different indoor envi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Furthermore, the particulate matter PM 10 and the CO 2 concentration were measured during school operation. Based on a computational model by [ 49 ] and the measurements of the study, it was determined that the potential amount of virus-laden particles inhaled by people in the room is reduced by a factor of 6 through the use of APs. Here, a highly infectious person was assumed to spend two hours with other people in a room where APs with a total air-circulation rate of 5.7 h −1 were in operation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the particulate matter PM 10 and the CO 2 concentration were measured during school operation. Based on a computational model by [ 49 ] and the measurements of the study, it was determined that the potential amount of virus-laden particles inhaled by people in the room is reduced by a factor of 6 through the use of APs. Here, a highly infectious person was assumed to spend two hours with other people in a room where APs with a total air-circulation rate of 5.7 h −1 were in operation.…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant discussion around role of aerosolized droplets, those with a diameter of <5 µm, and their ability to spread infectious virions across larger distances and times, and the need of ventilation systems to mitigate this potential route of transmission (5,98). A number of modeling studies have looked at various factors like droplet size, viral shedding rate, air flow, room dimensions, and types of ventilation systems to predict and highlight the potential risk of aerosolized transmission and infection in indoor environments (49,90,123,125). In the real world, unambiguous evidence of aerosolized transmission is difficult, but a number of outbreak studies have suggested that poor ventilation and air flow were contributing factors in SARS-CoV-2 transmission in a wide range of environments including food processing facilities (69), restaurants (96), apartment buildings (77), nursing homes (51) and hospitals (43), with environments like the latter, where infected individuals shedding high amounts of virus undergo procedures that would promote aerosolization, being a greater risk for such transmission.…”
Section: Assuring Proper Ventilation the Main Routes Of Sars-cov-2 Viral Transmission Are Viamentioning
confidence: 99%
“…A key parameter for evaluating certain measures or influences is the risk of infection. However, determining the risk of infection from airborne aerosols is itself subject to some uncertainty (Lelieveld et al, 2020). For this reason, we do not focus on the risk of infection for our subsequent assessments, but rather on the inhaled particle dose, which represents the number of virus-laden particles ingested by a person.…”
Section: Sensitivity Analysis Of the Influencing Parameters On The Particle Dose Potentially Inhaled By Individualsmentioning
confidence: 99%
“…Furthermore, the particulate matter PM10 and the CO2 concentration were measured during school operation. Based on a computational model by (Lelieveld et al, 2020) and the measurements of the study, it was determined that the potential amount of virus-laden particles inhaled by people in the room is reduced by a factor of 6 through the use of APs. Here, a highly infectious person was assumed to spend two hours with other people in a room where APs with a total air-circulation rate of 5.7 h -1 were in operation.…”
Section: Introductionmentioning
confidence: 99%